Developing an e-student worksheet on natural disasters to train elementary school students' scientific reasoning and environmental sensitivity - Putu Eka Suarmika; Nuris Hidayat; Mufarrahatus Syarifah; Afira; Nurul Arifa (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
An understanding of natural disasters that may occur in the environment around students is expected to facilitate their scientific reasoning by enabling them to explain natural phenomena using knowledge. This study aims to test the effectiveness of Science Student Worksheets on natural disasters in improving scientific reasoning skills and environmental sensitivity among fifth-grade Elementary School students. The research method used is the 4D Research & Development model. The results of the study show that the developed product is valid, effective, and practical in improving scientific reasoning skills and environmental sensitivity. The digital platform is an effective solution for 21st-century learning that focuses on enhancing high-level thinking skills and utilising digital learning technology.